Room temperature optical response of zinc oxide nanowires synthesized by chemical bath deposition to toluene vapors. Issue 5 (29th March 2016) - Apostoluk, Aleksandra; Parize, Romain; Vilquin, Bertrand; Nguyen, Trung‐Hieu; Consonni, Vincent; Appert, Estelle; Gaillard, François; Masenelli, Bruno
Abstract : Zinc oxide (ZnO) nanowires were synthesized by a simple and cost‐effective process, namely chemical bath deposition. X‐ray diffraction (XRD) pattern clearly shows that the nanowires are well crystallized in the wurtzite hexagonal structure. Field‐emission scanning electron microscope (FESEM) images show the formation of perfectly aligned and organized nanowires, with no defects visible on their surface. The diameter and length of nanowires is 65 and 850 nm, respectively. The room temperature UV‐excited photoluminescence spectra show the excitonic band in the UV and a wide emission band centered in the visible. This excitonic and visible emission is studied in the presence of toluene vapors and the results demonstrate the change of the visible photoluminescence of ZnO nanowire array and that the material is able to adsorb toluene. Finally, the mechanism of toluene sensing is discussed.